Ecotourism design and plant protection based on sensor network - Zhu, Jiang; Sun, JinChun (Frontiers in Plant Science, 2022)
National Forest Park is an important place for the public to carry out forest recreation activities and recognize natural habitats. With the popularization of forest tourism and the increase of forest recreational activities, the pressure on forest habitats has increased. The development of national forest parks is accompanied by opportunities and challenges. The main purpose of this paper is to analyze and study the impact of ecotourism design on plant protection based on sensor network technology. This paper analyzes the impact of tourism on the ecological environment, establishes an ecological environment monitoring system and an ecological tourism resource evaluation system, and studies the functional division of forest parks. Experimental research shows that, as a strictly protected area, the ecological conservation area basically does not conduct scenic spot development and resource mining, nor is it open to tourists. The total area is 852.92 hectares, accounting for 22.31% of the total area of the forest park, allowing the ecology of the ecological conservation area to achieve sustainable and healthy development.